2017
DOI: 10.1186/s12889-017-4888-1
|View full text |Cite
|
Sign up to set email alerts
|

Users’ experiences of wearable activity trackers: a cross-sectional study

Abstract: BackgroundWearable activity trackers offer considerable promise for helping users to adopt healthier lifestyles. This study aimed to explore users’ experience of activity trackers, including usage patterns, sharing of data to social media, perceived behaviour change (physical activity, diet and sleep), and technical issues/barriers to use.MethodsA cross-sectional online survey was developed and administered to Australian adults who were current or former activity tracker users. Results were analysed descriptiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
89
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(103 citation statements)
references
References 13 publications
7
89
0
7
Order By: Relevance
“…Mercer et al and Rosenberg et al both suggested that usability could be improved by having more compatible computers and smartphones, comprehensive paper manuals, and apps that interpret the user data. Studies among the elderly and adults [15][16][17][18][19][20][21][22][23][24][25][26][27][28] showed considerable similarities with the results of this study and those of Mercer et al and Rosenberg et al Older people and adults accepted the activity tracker, found them stimulating, increased awareness, and experienced them as useful. However, especially elderly stated they would prefer an activity tracker which is easier to use and adapted to their needs and skills.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Mercer et al and Rosenberg et al both suggested that usability could be improved by having more compatible computers and smartphones, comprehensive paper manuals, and apps that interpret the user data. Studies among the elderly and adults [15][16][17][18][19][20][21][22][23][24][25][26][27][28] showed considerable similarities with the results of this study and those of Mercer et al and Rosenberg et al Older people and adults accepted the activity tracker, found them stimulating, increased awareness, and experienced them as useful. However, especially elderly stated they would prefer an activity tracker which is easier to use and adapted to their needs and skills.…”
Section: Discussionsupporting
confidence: 82%
“…Feasibility aspects such as user-friendliness and sustained use of activity trackers have been studied in healthy adults [15][16][17][18][19][20][21][22] and the elderly [23][24][25][26][27][28]. From these studies it appears that in general, healthy adults and the elderly are open and positive towards the use of activity trackers.…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly mentioned disadvantages of the device were the short lifespan of the battery, the difficulty in synchronization and the inaccurately measured data. These findings are consistent with a previous work, in which (Maher et al, 2017) found that the battery lifespam was the participants' main complaint regarding activity trackers (Schaben, Furness, 2018).…”
Section: "I Have Knowledge About How Many Steps I Take and What My Slsupporting
confidence: 93%
“…With respect to validity and reliability, studies have demonstrated acceptable measurement properties of activity monitors [9], although limitations were noted in populations with low walking speed [10]. User acceptance of consumer activity trackers is high as a result of the technological improvements in functionality, appeal, and form factor [11,12]. As for the impact at point of care, a recent study by Birkeland et al [13] illustrated that wearable device-determined step count was able to determine treatment effect in patients with coronary microvascular dysfunction.…”
Section: Introductionmentioning
confidence: 99%